Knowledge & Attitude among Parents of Children with Bronchial Asthma whom Attending Iraq Pediatric Hospital - Al Quraini , Abrar Naser Hasan Ali (South Asian Journal of Social Sciences and Humanities, 2024)
Background: Asthma is a prevalent chronic condition in pediatric populations. The rising  incidence, morbidity, and mortality rates associated with asthma have heightened public  health concerns. Pediatric asthma imposes a substantial burden on affected children, their  families, and the broader community. Effective asthma management encompasses regular  monitoring, symptom control, and the prevention of exacerbations. Objectives: The study  aimed to document the knowledge, attitudes of parents of children with asthma and to  identify the factors associated with parent knowledge and attitude. Method: A study was  conducted involving 205 parents of children under five years old with asthma, who attended  the Karbala Pediatric Hospital between February 15 and May 15, 2023. A specially designed  questionnaire was utilized, comprising three sections: the first section addressed socio demographic information of both children and parents, the second section evaluated the  parents' knowledge, and the third section assessed the parents' attitudes. Responses were  scored with one point for correct answers and zero points for incorrect or "I don't know"  answers. Statistical analyses, including the Student's T-test, ANOVA, and linear regression,  were employed to identify factors associated with parental knowledge. Results: The results  indicated that the majority of participants were mothers, with a mean age of 29 years, and the  majority of asthmatic children were male (69.3%), with a mean age of 34.4 months. It was  found that 48.8% of participants had a poor knowledge score, while 61% had a poor attitude  score. Key factors influencing knowledge scores included the family’s place of residence, the  child’s birth order, the duration of the disease, the age at disease onset, the participant’s age,  and the mother's educational level. Conclusion: Overall, the parents demonstrated limited  knowledge and unfavorable attitudes regarding childhood asthma. Enhancing their  understanding and attitudes could potentially lead to improved management practices among  parents of children with asthma.
Keywords: Knowledge; Attitude; Children; Bronchial; Asthma; Iraq